Exploring barriers to physical activity participation among female nursing students adhering to specific social-cultural norms in Indonesia: A qualitative study - Koa, Apryadno Jose Al Freadman; Chou, Cheng-Chen; Lindayani, Linlin; Wang, Chi-Jane (Belitung Raya Foundation, Indonesia, 2024)
Background: The prevalence of insufficient physical activity is common among nursing students and impacts their academic performance. Research on obstacles to physical activity (PA) among religious women, notably Muslims, is limited. Objectives: This study aimed to explore barriers to PA among Indonesian Muslim female nursing students and gather suggestions for overcoming those barriers. Methods: This study used a qualitative descriptive design. Two focus groups were conducted with 12 Muslim female nursing students in Makassar, Indonesia. Interviews were audio-recorded and transcribed verbatim. The data were collected from May and July 2019. Inductive thematic analysis was used to identify core themes and sub-themes. Results: Thematic analysis identified barriers to PA across four main themes: intrapersonal, interpersonal, institutional, and social-cultural related to religious context. Each theme included two to three sub-themes, totaling nine categories of PA participation barriers. Intrapersonal barriers consisted of low motivation, emotional states, and a sedentary lifestyle. Interpersonal challenges included a lack of family or friend support and family obligations. Institutional barriers involved academic workload prioritization, school environment inaccessibility, and absence of athletic curriculum policy. Socio-cultural barriers posed by religious expectations included gender-related concerns and modest dressing. Drawing from their perspectives as Muslim female nursing students, study participants proposed six strategies to address these barriers. Proposed solutions include promoting PA through Apps, forming female team-up clubs, providing designated exercise spaces, and implementing mandatory athletic courses for nursing students at the institutional level. Additionally, offering female instructors and private exercise rooms could reduce the barriersfrom a socio-cultural perspective caused by religious expectations. Conclusions: The study found that Muslim female nursing students with dual roles face increased barriers to PA participation, driven by intrapersonal and interpersonal levels, nursing learning load, and religious norms. Schools could build environments to meet the religious expectations within Indonesian society to promote PA for Muslim female nursing students. For example, the practical strategies include offering private rooms or female instructors when they physically exercise in school.